MIMO techniques implementation on FPGA for future wireless transmission systems (4G/LTE) - Silva, Hugo Filipe Orfão da (2015)
This work alludes to 4G LTE technology. Techniques used for the same technology are described namely precoding and Alamouti coding and decoding. An Alamouti’s 4G system implemented to FPGA using the Xilinx System is introduced. The work also addresses the PAPR problem due to the reference pilots in the platform being generated all in phase. In this work a random pilot generator was implemented which combats the high peak power. In the receiver it was taken into account the new generation method to perform channel estimation correctly. A technique is discussed to increase the energy efficiency of the system based on PAPR reduction.